KNOWLEDGE, ATTITUDES AND PRACTICES REGARDING RABIES PREVENTION AND CONTROL AMONG PEOPLE RAISING DOGS AND CATS IN PHU TAN COMMUNE, CA MAU PROVINCE, 2025 (Vietnam Journal of Community Medicine, 2026)
Background: Rabies remains a serious public health problem in more than 150 countries and territories, with a 100% case fatality rate once clinical disease develops. Recently, it has re-emerged in Ca Mau Province and Phu Tan Commune.Objectives: This study aimed to determine the proportion of correct knowledge, attitudes, and practices (KAP) regarding rabies prevention and control, and to identify associated factors among dog and/or cat owners in Phu Tan commune, Ca Mau province in 2025.Materials and Methods: A cross-sectional descriptive study was conducted among 756 household representatives who owned dogs and/or cats from July to December 2025.Results: The proportions of respondents with correct knowledge, appropriate attitudes, and correct practices were 63.2%, 63.4%, and 46.7%, respectively. Multivariable logistic regression analysis showed statistically significant associations (p
Keywords: knowledge, attitudes, practices; rabies; rabies prevention and control.